Pengaruh Stress Kerja, Sikap dan Kecerdasan Emosional Terhadap Kinerja Perawat Di Ruang Rawat Inap RSUD Kota surakarta - Faradilla, Devy Nur; , Dr. Rusdi Lamsudin, Sp.S; , Drs. M. Farid Wajdi, MM.,Ph.D (2016)
The purpose of this study was to significant effect analysis: 1) work stress to nurse performance in treatment installation room at ARea Public Hospital of Surakarta 2) work attitude to nurse performance in treatment installation room at Area Public Hospital of Surakarta. 3)emotional intellegence to nurse performance in treatment installation room at Area Public Hospital of Surakarta. 4) work stres, work attitude and emotional intellegence simultaneous to nurse performance in treatment installation room at Area Public Hospital of Surakarta. Appropriate objectives so this study was using survey method by quantitative approach. This research population was all of nurse in treatment installation room at Area Public Hospital of Surakarta. Sample was taking 65 nurses by using total sampling technique. The main data collection tool using a questionnaire what relate the questionnaire from Sutrisno (2014), Carter (2010), and Indrayani (2015) and tested for validity and reliability in order to qualify a good measuring tool. Analysis tools used to test this hypothesis using Multiplled Regresion Analysis using SPSS 20.0 for Windows. Results of this study concluded: 1) Work stress has negative influence to nurse performance in treatment installation room at Area Public Hospital of Surakarta. 2) Work attitude has positive influence to nurse performance in treatment installation room at Area Public Hospital of Surakarta. 3) Emotional intellegence has positive influence to nurse performance in treatment installation room at Area Public Hospital of Surakarta. 4)work stres, work attitude, and emotional intellegence have an effect simultaneous to nurse performance in treatment installation room at Area Public Hospital of Surakarta.